Integrated evaluation of oxidation-reduction processes in rat liver tissues on the background of a mechanical eye injury - О. N. Pavlova; O. N. Gulenko; E. S. Korovina; V. V. Zaytsev (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
As a result of mechanical trauma to the eye and damage to the blood-ophthalmic barrier, an inflammatory process occurs and, as a result, oxidative stress is a state of the body that develops against the background of an overproduction of free radicals, with a violation of the effectiveness of antioxidant protection. The aim of the study was to study the dynamics of oxidative stress coefficients for the integral assessment of the antioxidant status of rat liver tissues under oxidative stress induced by mechanical eye trauma. The study was carried out on outbred white sexually mature healthy male rats of six months of age, weighing 220–240 g in the amount of 150 pieces. For the integral assessment of oxidative homeostasis in rats, the coefficients of oxidative stress were used: a coefficient expressing the ratio of catalase activity to SOD activity; antioxidant-prooxidant index (API), which expresses the ratio of catalase activity to MDA concentration; the coefficient of the ratio of the concentration of MDA to the concentration of DC and the local antioxidant index (LAI), which is the ratio of the product of the activities of catalase and SOD to the concentration of MDA. The study found that the antioxidant status of rat liver tissue under oxidative stress caused by mechanical trauma of the eye is most effectively stabilized by standard therapy of mechanical trauma of the eye with the addition of quercetin in the form of injections.